Bryozoa collected by the R.V. Falkor (too) during the 2025 cruise to the Mar del Plata Submarine Canyon, Southwest Atlantic - López-Gappa, Juan; Urteaga, Diego (Zootaxa, 2026)
Fourteen bryozoan species were collected during the 2025 cruise of R.V. Falkor (too) to the Mar del Plata Submarine Canyon (37.883333° S, 53.933333° W), at depths ranging between 1018 and 2628 m. Six species are considered new to science: Buffonella plana sp. nov., B. profunda sp. nov., Fenestrulina crassa sp. nov., Smittina amatista sp. nov., Parasmittina symmetrica sp. nov. and Orthoporidra claviformis sp. nov. For comparison, Patagonian shelf material of Buffonella simplex, a poorly known species described in the 19th century, is illustrated for the first time with scanning electron microscopy. The known geographic distributions of Microporella gappai and Smittoidea granulosa are expanded northwards. The bryozoan assemblage analysed in the present study has no species in common with the Magellanic bryozoan fauna inhabiting coastal and shelf areas of the Southwest Atlantic. On the contrary, the known distribution of most of these species is, so far, restricted to the continental slope off the Atlantic coast of southern South America. The bryozoan diversity of this Southwest Atlantic canyon is probably much higher than the assemblage documented in the present study.